Psychodrama Technique Group Guidance to Develop Positive Self-Concept for Students (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The problem in this study is the low self-concept of students which results in students becoming less confident, often comparing themselves with others, and not being able to identify themselves. This study aims to determine the effectiveness of group guidance services by using psychodrama techniques to develop students’ positive self-concept. This study uses a quantitative experimental method with a one group pretest posttest design. The population in this study is all students of class X (ten) MAN Dairi totaling 224 students with a sample of 8 (eight) students who have a low positive self-concept taken using a purposive sampling technique using a non-test instrument in the form of a questionnaire. The data analysis used was the Wilcoxon Signed Ranks Test with the results obtained an asymp significance value. Sig (2-tailed) is smaller (